PEMBUATAN SURFAKTAN SODIUM LIGNO SULFONAT DARI AMPAS TEBU - Farham HM Saleh; Andhika Dwi Cahaya Jumail; Fajrul Muhajirin (Teknoin, 2016)
Bagasse is one of the agricultural waste which is quite high at 19.7%. This research aims to assess the possibility of the use of bagasse as raw material for the manufacture of surfactants. Variable research is the concentration of NaHSO3 and long reaction time. The research was conducted using a three-neck flask reactor operated at 105 0 C and pH 4. Bagasse was pulverized to 120 mesh size, extracted with methanol for isolation of lignin. Furthermore, lignin reacted with NaHSO3 in a threeneck flask at 105 0C and pH 4. The results showed that the greater the concentration NaHSO3 and the longer the reaction time, the amount of lignosulfonates produced even greater. The optimum condition was obtained at a concentration of 30% NaHSO3 and the long reaction time of 60 minutes to produce the amount of lignosulfonate 17209.238 ppm or a yield of 20.717%.